Нейронні мережі в задачах прогнозування в меліорації - Медиковський, М.; Опотяк, Ю. (Видавництво Національного університету “Львівська політехніка”, 2001)
Розглядається задача прогнозування рівня грунтових вод в меліоративних системах з використанням технологій нейронних мереж. Описано постановку ряду задач, методику підготовки даних, наведено приклади їх успішного вирішення.

The problem of forecasting ofparameters of a water regime of ground on reclaimed grounds with applying of know-how of neural networks is considered. The know-how of neural networks under condition of selection of adequate model are capable to execute forecasting of water regimes of grounds with adequate accuracy and will allow to establish complementarity and influencing of these parameters on a groundwater level. Problem set, data preprocessing for neural net learning and solutions of a few sample problems are presented.
Keywords: 621.142.4